2013
DOI: 10.1017/s0033291713002584
|View full text |Cite
|
Sign up to set email alerts
|

Temporal discounting in major depressive disorder

Abstract: BackgroundMajor depressive disorder (MDD) is associated with abnormalities in financial reward processing. Previous research suggests that patients with MDD show reduced sensitivity to frequency of financial rewards. However, there is a lack of conclusive evidence from studies investigating the evaluation of financial rewards over time, an important aspect of reward processing that influences the way people plan long-term investments. Beck's cognitive model posits that patients with MDD hold a negative view of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
142
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(156 citation statements)
references
References 37 publications
11
142
3
Order By: Relevance
“…Developmental studies found thatncreased fronto-striatal activation with development correlates with decreased delay discounting (121, 122). Recent studies found that both adult patients with MDD (123) and with BD (124) exhibit steeper discounting during a delay discounting task relative to healthy controls. Altogether these results suggest altered appraisal of future rewards in MDD and BD that may have implications for treatment approaches.…”
Section: Current Research Of Circuit Interactions In Mood Disordersmentioning
confidence: 99%
“…Developmental studies found thatncreased fronto-striatal activation with development correlates with decreased delay discounting (121, 122). Recent studies found that both adult patients with MDD (123) and with BD (124) exhibit steeper discounting during a delay discounting task relative to healthy controls. Altogether these results suggest altered appraisal of future rewards in MDD and BD that may have implications for treatment approaches.…”
Section: Current Research Of Circuit Interactions In Mood Disordersmentioning
confidence: 99%
“…Our recommended uninformative prior, for rewards in the order of £100, was based on a brief survey of the literature including Green, Myerson, Lichtman, Rosen, and Fry (1996), Pulcu et al (2013), and Decker et al (2015). Values of log(k) range from approximately −2.5 (bipolar disorder) to approximately −6 (anorexia nervosa).…”
Section: Experiments Typementioning
confidence: 99%
“…We simulated participants with high, medium and low temporal discounting (rows). Discount rates used correspond to those with major depressive disorder (k = 0.04, half life of 25 days, Pulcu et al, 2013), upper income older adults (k = 0.01, half life of 100 days, Green et al, 1996), and those with anorexia nervosa (k = 0.0028, half life of 357 days, Decker et al, 2015). These examples provide an overview of the different methods in terms of how their experimental designs (points) unfold.…”
Section: Experiments Typementioning
confidence: 99%
“…These studies have found evidence for steeper discounting amongst patients with symptoms of schizophrenia (Heerey et al, 2007(Heerey et al, , 2011Ahn et al, 2011;MacKillop and Tidey, 2011;Wing et al, 2012;Avsar et al, 2013;Weller et al, 2014), depression (Takahashi et al, 2008;Dennhardt and Murphy, 2011;Dombrovski et al, 2012;Imhoff et al, 2014;Pulcu et al, 2014), mania (Mason et al, 2012), attention deficit hyperactivity disorder (ADHD) (Barkley et al, 2001;Tripp and Alsop, 2001;Bitsakou et al, 2009;Paloyelis et al, 2010a,b;Scheres and Hamaker, 2010), anxiety disorder and cluster B personality disorder (Dougherty et al, 1999;Moeller et al, 2002;Petry, 2002;Dom et al, 2006a,b;Lawrence et al, 2010;Coffey et al, 2011). This line of enquiry is not without theoretical justification, for example the broader construct of impulsivity, defined as taking action without forethought or regard for consequences (Moeller et al, 2001), of which discounting is an element, is a defining feature of some psychiatric disorders, for example borderline personality disorder (Moeller et al, 2001;DSM V, 2013) and mania (Swann, 2009).…”
Section: Vitae Summa Brevis Spem Nos Vetat Incohare Longammentioning
confidence: 99%
“…This idea might hold relevance for increased discounting in depression, which is associated with both marked avoidance (Ferster, 1973) and possible serotonergic abnormalities (e.g., Mann et al, 2000). Although a normative account of the role of serotonin in depression remains elusive, it is interesting that decreasing serotonin availability (achieved by tryptophan depletion) in healthy subjects acts to increase discounting (Tanaka et al, 2007;Schweighofer et al, 2008), commensurate with increased discounting seen in depression (Takahashi et al, 2008;Dennhardt and Murphy, 2011;Dombrovski et al, 2011Dombrovski et al, , 2012Imhoff et al, 2014;Pulcu et al, 2014) (For further discussion of temporal preferences for punishment see Berns et al, 2006;Story et al, 2013Story et al, , 2015.…”
Section: Future Directionsmentioning
confidence: 99%